FUNCTION AND MEANING OF GONDRANG SIPITU-PITU IN THE LAYUR MATUA CEREMONY IN THE SIMALUNGUN COMMUNITY IN HARANGGAOL HORISON DISTRICT - Situmeang, Kasri; Sebayang, Vanesia Amelia; Ginting, Pulumun P (Universitas Negeri Medan, 2025)
This article is entitled